تحديد درجة حرارة الوسيط العامل في أنابيب الضاغط بالاعتماد على درجة حرارة السطح الخارجي للأنبوب - نصرة عواطف (Latakia University Journal -Engineering Sciences Series, 2019)
This study shows the method or method of determining the temperature of the medium in the compressor tubes by the measured temperature of the pipe walls or pipes of transport. The heat transfer conditions can vary and are markedly different for different tubes and the calculated temperatures and temperatures are designed and adjusted according to the different investment conditions of the tube. The calculation of the temperature calculation software was completed and adjusted to determine the temperature of the medium inside the pipe according to the temperature of the outer wall of the tube. All factors affecting the temperature (convection heat transfer coefficient from the center inside the tube - wall thickness - pollution) were analyzed. This method was chosen on a navigational compressor unit where the temperature of the medium inside the tube was determined at the temperature of the tube surface. Taking into account the corrections, regulation or adjustment of the measuring instruments that have been accomplished and which determine the temperature of the pipe walls. They can be used as additional means of measurement, increased accuracy of control and control results, analysis of work systems and increased reliability of navigational pipeline investment. تبين هذه الدراسة اسلوب تحديد درجة حرارة الوسط في أنابيب الضاغط عن طريق درجة الحرارة المقاسة لجدران الأنبوب أو مواسير النقل. إن شروط انتقال الحرارة يمكن أن تختلف وتتميز بشكل كبير لمختلف الأنابيب والأوساط ودرجات الحرارة المحسوبة. درجات الحرارة صُممت وعُدلت حسب ظروف الاستثمار المختلفة للأنبوب. للحساب تم انجاز برنامج حاسوبي مكتوب من مجموعة رياضية، درجات الحرارة المحسوبة مصممة ومعدَّلة لتحديد درجة حرارة الوسط داخل الأنبوب وذلك حسب درجة حرارة الجدار الخارجي للأنبوب. حيث تم تحليل جميع العوامل المؤثرة على درجات الحرارة (معامل انتقال الحرارة بالحمل من الوسط داخل الأنبوب– سماكة الجدران- التلوث). تم اختيار هذه الطريقة على وحدة ضاغط ملاحي حيث امكانية تحديد درجة حرارة الوسط داخل الأنبوب عند درجة حرارة سطح الأنبوب. مع الأخذ بعين الاعتبار التصحيحات والتنظيم أو الضبط لأجهزة القياس التي تم انجازها والتي تحدد درجة حرارة جدران الأنابيب. ويمكن أن تُستخدم كوسائط إضافية للقياس وزيادة دقة نتائج التحكم والمراقبة، تحليل أنظمة العمل وزيادة وثوقية استثمار أنابيب الملاحية.